Design and analysis of FRP composite bolted joints for space structures - et.al, Dr. G. V. R. Seshagiri Rao (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Man tries to learn his surroundings by showing tendencies such as discovering, researching, asking questions, and noticing the relationships between objects. In other words, he tends to understand the world he lives in with various judgments. Therefore, it is important to raise individuals with advanced reasoning skills, mathematical thinking skills, proofing skills, problem solving skills, metacognitive knowledge, skills or qualifications. It can be said that this can only be possible with the right teaching models, methods, techniques and teachers who can use them in the most efficient way. In this context, the aim of the study is; To determine the difficulties in the preparation process for LGS, which has been implemented in our country since 2018, and the reflections of LGS on mathematics education applied in schools within the framework of the opinions of mathematics teachers and make suggestions accordingly. In the study, the screening model was adopted because it was tried to portray the thoughts of a certain group of participants on a subject. The sample of the study; It consists of 110 mathematics teachers who attended 8th grade classes in the 2018-2019 academic year. The data obtained from teachers' opinions were analyzed by content analysis method. According to this; The predominant opinion is that students have problems in understanding, interpreting, thinking and reasoning in the new examination system, however, because the textbooks and the exam are not parallel, teachers have various difficulties. In this direction, various activities can be organized to increase students' motivation and to gain reading habit. In addition, it is thought that it would be beneficial to provide teachers with in-service training for the exam.